(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Sun drying of fish is an important method of fish preservation throughout the world. Due to its availability and product specific flavor and texture, dried fish has become an important part in the diet of people living particularly in the coastal region of many Asian countries including Bangladesh. Product type is considerably wide depending on the season, availability of fish, infrastructure and technical know-how of the processors. These are mainly processed from marine fishes that are caught by the artisanal fishermen and marketed throughout the country by multistep marketing channel up to reaching to the consumer. Due to the importance of the product in terms of market volume as well as its major role in the socio-economic condition of millions of people of the country, the sector needs proper attention by appropriate authorities to ensure quality and safety of the product produced and marketed. In this paper, different methods of sun drying practiced traditionally in the coastal region of Bangladesh and associated marketing systems are reviewed. It is expected that training of processors on Sanitation Standard Operating Procedures and monitoring by appropriate government body would be necessary to improve quality and simultaneously ensure safety of sun-dried fish produced in the coastal region of Bangladesh. Res. Agric., Livest. Fish.5(3): 381-390, December 2018